SOVEREIGN WEALTH FUNDS AND THEIR ROLE IN MANAGING MACROECONOMIC VARIABLES AND SUPPORTING ECONOMIC INVESTMENT (World Economics and Finance Bulletin, 2025)
Sovereign funds are financial funds belonging to countries that are used to confront economic crises, support economic variables, and promote the developmental reality funded by the financial surpluses achieved by countries in the various economic resources that belong to them. Sovereign funds are considered one of the procedures followed to benefit from financial surpluses and use them to support local investments, achieve qualitative shifts in macroeconomic variables, and make it a dynamic engine for economic investments, thus achieving economic diversification for countries , due to the abundance of the Iraqi economy in its natural, rentier, geological and human resources, as well as its geographical location and the economic, political and social potentials it achieves. This requires the need to pay attention to following wise mechanisms and policies to manage the diverse resources in the Iraqi economy, promote its macroeconomic reality, and create a strong economic environment with effective macroeconomic variables. Therefore, it is necessary to have funds that support these policies represented by sovereign funds, reduce dependence on rentier revenues, and take advantage of their surpluses in making the macroeconomy more effective and dynamic .
Keywords: Sovereign funds; Investment trends of sovereign funds; Types of sovereign funds